ANALISIS PENGARUH KUALITAS PRODUK, HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR YAMAHA PADA YAMAHA SEMARANG - Nico Martiyanto Bayuaji, 08.3502.0508; Maskur, Ali (Students Journal of Economic and Management, 2012)
The purpose of research is to discover, develop and test a knowledge of the truth. Thus, this research is an activity to obtain information about consumer purchasing decisions on Yamahaproducts. In this study population is all the people who have bought Yamaha motorcycles in Semarang. The sampling technique used in this study was purposive sampling. The samples used were 100 people who have bought motorcycles Yamaha Yamaha dealer Semarang Based on the results of model calculations derived summary size adjusted R2 is 0.922 this means that 92.2% of purchase decisions variation can be explained by the variation of the three independent variables, namely the quality of the product, price and promotion. From the results of multiple regressionanalysis can be seen that the positive effect on the quality of the product purchase decision. The effect was statistically significant at probability of 0.000 (sig / p <0.005). Prices have a positive and significant impact on purchasing decisions. The effect was statistically significant at probability of 0.000 (0.000 <0.05) and the promotion of positive effect on keptusan purchase. The effect was statistically significant at the probability obtained less than 5% Î± (0.000 <0.05). It is identified that all the hypotheses accepted or proven.